Taxpayer Awareness as a Moderating Variable of The Influence of Tax Compliance on Tax Revenue - Hardiansyah, Hardiansyah; Dewanti, Yopy Ratna; Ervina, Nelly; Nasution, Amsal; Judijanto, Loso (Innovative: Journal Of Social Science Research, 2025)
Abstract This research is a quantitative study with an explanatory approach, namely an approach that places the burden of proving the hypothesis on previous studies, especially the three studies mentioned above. The data in this study is secondary data obtained from the tax website go.id in the last Five years (Abdurahman 2016). The data obtained was analyzed using the PLS 4.0 smart analysis tool . The result in this article show the hypothesis that the researcher has in this study aims to analyze the effect of the Tax Compliance variable on Tax Revenue can have a positive relationship direction and a significant influence because the P-Values ​​value is positive and is below the significance level of 0.05, namely 0.004. This means that by increasing Tax Compliance, the more people pay taxes, the more tax revenues can also increase. Furthermore, in the second column, the Taxpayer Awareness variable can also moderate the effect of the Tax Compliance variable on the Tax Revenue variable because the same thing is that the -Values ​​value is positive and is below the significance level of 0.05, namely 0.000 and is more significant than direct testing 0.004. This means that if tax compliance can increase tax revenue by ninety-four percent, then moderate taxpayer awareness can increase tax revenue by one hundred percent. Keyword: Taxpayer Awareness, Tax Compliance, Tax Revenue